Supervisi Akademik Pengawas dalam Meningkatkan Profesionalisme Guru Pendidikan Agama Islam Sekolah Umum di Kabupaten Malang - Arito (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This research was conducted with the aim to describe the planning of academic supervision, the strategy for implementing academic supervision and the evaluation of academic supervision carried out by PAI supervisors in increasing PAI teacher professionalism in public schools in the Malang district. The research design used was case study method with a qualitative approach. The participants enrolled in this study were PAI supervisors, PAI teachers, school principals, and curriculum representatives. The data collection techniques used were interviews, observations, and documentation. Data analyses used were based on Miles, Huberman and Saldana theory which consisted of data collection, data condensation, data presentation, and conclusion/verification. The results show that: (1) the academic supervision planning which is carried out at the beginning of the year is based on the Pokjawas PAI programs and the evaluation results of the PAI supervisor program in the previous year; (2) the academic supervision is carried out individually and classically with a friendliness approach. In individual supervision, PAI supervisors conduct assessment of learning administration, RPP, learning implementation in the class, and learning assessment. In classical supervision, PAI supervisors provide guidance on the preparation of learning administration, IT-based learning models and media, and learning assessment; (3) the result evaluation of academic supervision is conducted by analyzing the results of academic supervision. The advantages and disadvantages of academic supervision findings are directly communicated to PAI teachers and principals to follow-up. Good findings should be maintained and improved, while poor findings should be corrected with the guidance of PAI supervisors.